Mitigating science and aggravating beliefs of pandemics (Journal on studies and research of academic knowledge, 2022)
The present work is a critical review of the relationships that link science and technology, with society. It analyzes the evolution of paradigmatic technology (ICT), the socio-political changes that this brought about and its impact on pandemics. It proposes the employs specialized bibliographic research and documentary analysis in order to carry out a diagnosis of contemporaneity and, from here, to propose strategies for solving the social problem posed by the pandemic crisis from the perspective of “Science, Technology and Society” (STS). This study challenges the current way of doing science and technology. It proposes the inclusion of conceptual, procedural and instrumental innovations, based on new paradigms, such as the social appropriation of science for participation in scientific-technological decisions and the democratic choice of the destinies of society. All of this points to equal access to technological-health resources that allow us to effectively combat pandemics and adversities in general, as well as live in socio-environmental harmony
Keywords: Public policies; Programmed obsolescence; Social appropriation of science